Genomic Analysis Reveals Human-Mediated Introgression From European Commercial Pigs to Henan Indigenous Pigs - Wang, Kejun; Zhang, Lige; Duan, Dongdong; Qiao, Ruimin; Li, Xiuling; Li, Xinjian; Han, Xuelei (Frontiers in Genetics, 2021)
Introgression of genetic features from European pigs into Chinese pigs has contributed to improvements in productivity traits, such as feed conversion efficiency and body size. However, the genomic differences and potential role of introgression in Henan indigenous pigs are unclear. In this study, we found significant introgression from European pigs into Chinese indigenous pigs, especially in Henan indigenous pigs. The introgression in Henan indigenous pigs, particularly in Nanyang black pigs, was mainly derived from Duroc pigs. Most importantly, we found that the NR6A1, GPD2, and CSRNP3 genes were introgressed and reshaped by artificial selection, and that this may have contributed to increases in pig body size and feed conversion efficiency. The results suggest that human-mediated introgression and selection have reshaped the genome and improved desired traits. These findings will contribute to our understanding of the history of Henan indigenous pigs and will provide insights into the genetic mechanisms affecting economically important traits of pigs.